CHRISTIAN CONCEPT OF PERSON AND HUMAN DIGNITY IN THE INDIAN CULTURAL CONTEXT: A Systematic Study Based on the Modern Social Encyclicals - Padamadan, Lawrence Thomas (Asian Horizons, 2020)
University/Institution: Philosophisch-Theologische Hochschule Vallendar (PTHV), Germany Faculty/Department: Theology Director of the Doctoral Dissertation: Prof. Dr George Augustin, SAC Year of Doctoral Defence: 2019